Profibrotic Signaling Pathways and Surface Markers Are Up-Regulated in Fibroblasts of Human Striae Distensae and in a Mouse Model System. Issue 2 (6th June 2022) - Borrelli, Mimi R.; Griffin, Michelle; Chen, Kellen; Deleon Diaz, Nestor M.; Adem, Sandeep; Mascharak, Shamik; Shen, Abra H.; Ngaage, Ledibabari Mildred; Lewis, Nicolette; Longaker, Michael T.; Gurtner, Geoffrey; Wan, Derrick C.; et al.
Abstract : Background: Striae distensae are common disfiguring cutaneous lesions but lack effective treatments because of an incomplete understanding of their pathophysiology. Dermal fibroblasts likely play an important role. The authors investigate the cellular-molecular features distinguishing fibroblasts from human striae distensae and normal skin. The authors also develop a mouse model of striae distensae. Methods: Human striae distensae and normal skin samples were compared for tensile strength and histologic structure. Fibroblasts from striae distensae and normal skin were isolated by fluorescence-activated cell sorting for gene expression analysis. Immunofluorescence staining and fluorescence-activated cell sorting were used to confirm gene expression data at the protein level. A mouse model of striae distensae formation was created by administering corticosteroids and mechanically loading the dorsal skin. Results: Human striae distensae exhibited reduced tensile strength, more disordered collagen fibers, and epidermal atrophy compared to human normal skin. There were 296 up-regulated genes in striae distensae fibroblasts, including the profibrotic lineage and surface marker CD26. Up-regulated genes were involved in profibrotic and mechanoresponsive signaling pathways (TGFβ and FAK-PI3-AKT-signaling). In contrast, 571 genes were down-regulated, including CD74 and genes of the AMPK pathway. Increased CD26 and decreased CD74 expression was confirmed by fluorescence-activated cell sorting and immunofluorescence. Similar cutaneous histologic and gene expression changes were induced in hypercortisolemic mice by mechanically loading the dorsal skin. Conclusions: Fibroblasts from human striae distensae exhibit increased profibrotic and decreased antifibrotic signaling. CD26 and CD74 are promising surface markers that may be targeted therapeutically. The authors' mouse model of striae distensae can be used as a platform to test the efficacy of potential therapeutic agents. Clinical Relevance Statement: Striae distensae are common disfiguring cutaneous lesions whose etiology remains elusive, which has hindered development of effective treatment strategies. Dermal fibroblasts likely play an important role. The authors sought to elucidate the key cellular-molecular pathways distinguishing fibroblasts in striae distensae from those in normal skin.